If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-1/3(6y+6)+2=3y
We move all terms to the left:
-1/3(6y+6)+2-(3y)=0
Domain of the equation: 3(6y+6)!=0We add all the numbers together, and all the variables
y∈R
-3y-1/3(6y+6)+2=0
We multiply all the terms by the denominator
-3y*3(6y+6)+2*3(6y+6)-1=0
Wy multiply elements
-9y^2(6+6y(6-1=0
| 30+1x-(10x+3x)=88 | | 30-12x=88 | | 18x-7=2x | | 6x18-4x=3x+14x9x6 | | 2.5=5/x-5 | | x+x/7=27 | | 6x+9+x+3=110 | | -4x+2x-3=15 | | 2x5=x+14 | | 800(52-x)-500(54+x)=17200 | | 9x^2-200x+455=0 | | 78x7=546 | | 78x6=468 | | 88x4=352 | | 83x4=332 | | 82x9=738 | | 81x9=729 | | 94x6=564 | | 72x9=648 | | 74x7=518 | | 99x7=693 | | 66x5=330 | | 98x4=392 | | 97x4=388 | | 89x4=356 | | 77x6=462 | | 99x6=594 | | 5(2x-3)=-20 | | 99x4=396 | | 2z+3=6+2z | | 7x+9=7+3x | | 5t-4=4t-6 |